Overview of Physical Climate Risks and Their Impact on the Economy and Financial System of Croatia - Srdelic, Leonarda (Oeconomica Jadertina, 2024)
This paper employs an interdisciplinary approach, merging climatology with economic and financial analysis, to deepen understanding of how climate change affects the economy and financial system of Croatia. Using geospatial analysis of data from the IPCC and Copernicus programmes, we have identifed regions within Croatia variably exposed to climate risks, enabling more precise risk assessments for banks and financial institutions. The work also contributes to the theoretical understanding of the relationships between climate change and macroeconomic variables and provides a framework for analysing the long-term economic effects of climate change. The research results can serve as a basis for developing adaptation and mitigation strategies to climate risks at the national level. Specifically, this paper also serves as a data source for formulating policies aimed at reducing the economy’s vulnerability to climate change.